Financial Determinants of Human Development in Developing Countries - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2011)
Hitherto financial drivers of human development have been unexplored by the UNDP. This paper assesses determinants of human development from financial dynamics of depth, efficiency, size and activity on data from 38 developing countries. While the importance of financial activity, size and depth (in decreasing order) is significant for inequality adjusted human development, financial allocation efficiency significantly undermines welfare. As a policy implication results do not support financial allocation efficiency as a driver of human development.
Keywords: E00; G20; I00; O10; 330; Banking; human development; developing countries; instrumental variables